DIAGNOSIS OF SPIRITUAL EDUCATION OF STUDENTS SENIOR CLASSES (Pedagogy of Higher and Secondary Education, 2022)
The diagnostic methods of senior pupils spiritual development are exposed in the article.
Keywords: 1